2021
DOI: 10.1177/00307270211021875
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on sustainable agricultural practices among oil palm farmers

Abstract: Oil palm farmers play an important role in ensuring oil palm cultivation can achieve sustainable agricultural practice. However, the best agricultural practices among oil palm farmers are yet to be known. This study aims to systematically review oil palm farmers’ sustainable practices. The present study integrated multiple research designs and the review was based on the published standard, namely ROSES (Reporting Standards for Systematic Evidence Syntheses). This study used Web of Science (WoS) as the main da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This step is crucial to mitigate bias and pinpoint potential articles with methodological shortcomings (Seehra et al, 2016). Following the recommendation of Abas et al (2022), two evaluators were designated among the researchers for this assessment. The evaluators will categorize the articles into three quality tiers: high, moderate, and low.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…This step is crucial to mitigate bias and pinpoint potential articles with methodological shortcomings (Seehra et al, 2016). Following the recommendation of Abas et al (2022), two evaluators were designated among the researchers for this assessment. The evaluators will categorize the articles into three quality tiers: high, moderate, and low.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Of the 100 articles indexed by Scopus, they can be grouped into 3 clusters which can be identified by color node each keyword. Cluster 1 is symbolized in red and includes terms related to studies with keywords Farmer [1][2][3][4][5][6], Standard [7][8][9][10], Impact [11][12][13] , Access [14], ISPO [15][16][17][18][19] it can be interpreted that the studies on the cluster referred to one and the other study keywords often intersect and tend to have links, for example research with studies on financial and benefits certification on one the articles in the study cover a lot of discussion related to the keywords impact, farmer and standards Cluster 2, which is symbolized in yellow, consists of studies that tend to lead to one keyword, namely RSPO certification [20][21][22][23][24][25][26], Cluster 3, which is symbolized in blue, consists of Oil Palm studies [27,28], Deforestation, Plantation, Biodiversity and Cluster 4 which is symbolized in green consists of MSPO certification studies, Industry, Independent Smallholder, Implementation. From the visualization of the network visualization, there is an interesting thing, namely that there is a high link to the study with the keywords of sustainable oil palm plantation certification namely ISPO, RSPO, and MSPO during the period from 2006 to 2023…”
Section: Network Visualizationmentioning
confidence: 99%
“…There are five (5) themes for sustainable practices in agriculture industry namely, land management, waste management, advance technology, economic empowerment, and social inclusion (Abas et al, 2021). The study found that sustainability certification and its underlying principles is one of the methods to achieve all five themes of sustainability practices.…”
Section: Literature Reviewmentioning
confidence: 99%